IDENTIFYING AND MAPPING POTENTIAL GROUNDWATER USING THE 1-D GEOELECTRIC RESISTIVITY METHOD AT BOA VILLAGE, ROTE NDAO REGENCY,EAST NUSA TENGGARA - Arief, Muhammad; Suwandi, Suwandi; Kustiawan, Eko; Marsun, Marsun; Utami, Dian; Yakin, Nurman (Journal of Industrial Engineering & Management Research, 2025)
Water is a basic human need. Population in Rote Regenscy growth up very fast led to increased water demand, but water management does not meet the required quantity. Therefore, research is needed to map groundwater potential for clean water supply for the community. This research was conducted in Boa Village, Rote Barat Distric, Rote Ndao Regency, East Nusa Tenggara. The purpose of this study was to determine the groundwater potential in the aquifer and the lithology type, depth, and thickness of the groundwater aquifer based on the resistivity of the rock types. Data acquisition in this study was conducted using the Schlumberger 1-D geoelectric method. Measurements were taken at three sounding points with a span of 40–50 meters. Based on the results of the 1D Ip2Win data processing, it was determined that the subsurface lithology of the study area consists of top soil, overburden, coral reff, rock , limestone, and sand.